ANALISIS OPINI PUBLIK TENTANG PEMBERIAN REMISI KEPADA PARA NARAPIDANA KORUPTOR: ANALISIS OPINI PUBLIK TENTANG PEMBERIAN REMISI KEPADA PARA NARAPIDANA KORUPTOR - Herdiansyah Amanu (Universitas Sumatera Selatan, 2021)
Corruption is a crime that against the law and causes many bad effects that do not harm the state, but also torment the people. The polemic about whether the corrupt convicts deserve to get remission, still become discourse in this country. This research try to expose the public opinion that’s in case represented by the public in Palembang, about 2 things: 1) it’s proper or not if the corrupt convicts are given remission, 2) what proper punishment is given to the corrupt convicts. This research uses descriptive qualitative method. As the result of research and discussion, it can be concluded that the public tend to judge the corrupt convicts are not proper to get remission. It’s seen from most of the informants, namely 9 persons (90% informants) express they’re not proper to get remission. Only 1 person (10% informants) express they’re proper to get remission. Meanwhile about the properest punishment that’s given to the corrupt convicts is the punishment that’s suitable with the applicable law. It’s seen from most of the informants, namely 9 persons (90% informants) agree the corrupt convicts are punished suitable with the applicable law. Only 1 person (10% informants) wants the different punishment, namely the death punishment for the corrupt convicts